Application of different hardware and software in the concept of digital pilot training and selection - Aleksandar Z. Knežević; Aleksandar G. Bukvić; Branimir B. Krstić (Vojnotehnički Glasnik)
Introduction/purpose: In many military air forces and civil aviation organizations that use or own training aircraft equipped with a digital cockpit, training tools such as trainers and simulators are understood to a varying extent. Special attention is paid to the ratio of hours spent training on the real aircraft to the number of hours spent on the simulator. This approach in training professional circles and the public is called Live Virtual Constructive. For all other teaching aids used for preparation for training, neither the methodology nor the extent of their use has been specifically investigated. The research aims to develop instruments that will measure and evaluate the success and qualitative progress in pilot training achieved by using the digital cabin space, based on which a decision can be made about further training for a specific aircraft type. Methods: In conjunction with a PC-based aviation training device and advanced statistical analyses, an eye movement tracking device will help arrive at a reference pattern of instrument observation to train pilots and select pilot candidates.